Legal integration and language diversity : rethinking translation in EU lawmaking - Baaij, Cornelis J. W. <<[VerfasserIn]>> (Oxford University Press, 2018)
Introduction -- Articulating the task of EU translation -- Formalizing the primacy of English -- The mixed approach of current EU translation -- Considering a source-oriented alternative -- The implementation and its challenges
Includes bibliographical references and index
Based on author's thesis (doctoral - Universiteit van Amsterdam, 2015)